The beginnings of tool innovation in human ontogeny: how three- to five-year-olds solve the vertical and horizontal tube task - Breyel, Sabine; Pauen, Sabina (Cognitive development, 2021)
This study focuses on tool innovation in preschoolers. It extends previous work by investigating task- and age-related changes in success rates, latency to success, and solution strategies. Three- to five-year-olds had 10 min to retrieve a toy from either a horizontal or a vertical tube by manufacturing a tool from multiple materials. In the Horizontal Tube Task, success rates were high irrespective of age. Solution strategies revealed mainly second-order innovation (i.e., manipulating materials while retrieving the toy). In the Vertical Tube Task, success rates increased with age and solution strategies reflected mainly first-order innovation (i.e., manufacturing the tool before trying to retrieve the toy). In the Vertical Tube Task, children needed more time to find a solution, with first-order innovation tending to be faster than second-order innovation. These findings demonstrate the potential of young preschoolers to innovate tools when given enough time, but also a high task-dependency of performance.
Gesehen am 01.07.2021